Polymer-based antibody mimetics (iBodies) target human PD-L1 and function as a potent immune checkpoint blocker - Zamani, Mohammad Reza; Hadzima, Martin; Blažková, Kristýna; Šubr, Vladimír; Ormsby, Tereza; Celis-Gutierrez, Javier; Malissen, Bernard; Kostka, Libor; Etrych, Tomáš; Šácha, Pavel; Konvalinka, Jan (The Journal of biological chemistry, 2024)
Immune checkpoint blockade (ICB) using monoclonal antibodies against programmed cell death protein 1 (PD-1) or programmed death-ligand 1 (PD-L1) is the treatment of choice for cancer immunotherapy. However, low tissue permeability, immunogenicity, immune-related adverse effects, and high cost could be possibly improved using alternative approaches. On the other hand, synthetic low-molecular-weight (LMW) PD-1/PD-L1 blockers have failed to progress beyond in vitro studies, mostly due to low binding affinity or poor pharmacological characteristics resulting from their limited solubility and/or stability. Here, we report the development of polymer-based anti-human PD-L1 antibody mimetics (α-hPD-L1 iBodies) by attaching the macrocyclic peptide WL12 to a N-(2-hydroxypropyl)methacrylamide copolymer. We characterized the binding properties of iBodies using surface plasmon resonance, enzyme-linked immunosorbent assay, flow cytometry, confocal microscopy, and a cellular ICB model. We found that the α-hPD-L1 iBodies specifically target human PD-L1 (hPD-L1) and block the PD-1/PD-L1 interaction in vitro, comparable to the atezolizumab, durvalumab, and avelumab licensed monoclonal antibodies targeting PD-L1. Our findings suggest that iBodies can be used as experimental tools to target hPD-L1 and could serve as a platform to potentiate the therapeutic effect of hPD-L1-targeting small molecules by improving their affinity and pharmacokinetic properties.
Keywords: tumor immunology; Immune Checkpoint Inhibitors; Cell Line, Tumor; B7-H1 Antigen; Antibodies, Monoclonal; Polymers; lidé; PD-1; inhibitor; immunosuppression; inhibitory kontrolních bodů; T-cell; immune checkpoint; polymery; PD-L1; HPMA copolymer; antibody mimetic; antigeny CD274; monoklonální protilátky; immunotherapy; nádorové buněčné linie; Humans